Comprehensive investigation into the effects of oxygen concentration on pyrite oxidation processes and key ion migration patterns in black rock layers - Zihang Liu; Zhangjun Dai; Fei Yu; Kaiwen Tong; Jianhua Guo; Kang Huang; Shanglin Qin; Shanxiong Chen (Case Studies in Construction Materials)
This study systematically analyzed the impact of oxygen concentration on the oxidation of black rock layer samples and the migration patterns of key ions, focusing on samples from a high-speed railway subgrade in Fenghuang County, Hunan Province. The experimental results identified three stages of sample oxidation, showing that oxygen concentration significantly influences the reaction rate during the initial stage. Under high oxygen concentration, the generation rate of sulfate ions (SO42−) rapidly peaks in the early phase. Although this initial phase only accounts for 8 % of the entire oxidation process, it constitutes 77 % of the overall reaction. After this peak, the rate gradually decreases and stabilizes. While the oxidation rate is slower under medium and low oxygen concentrations, the overall trend remains similar to that observed under high oxygen conditions. The study also revealed that fill material samples are particularly sensitive to oxygen concentration during the early stages of oxidation, whereas the oxidation process in parent rock samples is significantly delayed due to their long-term undisturbed state and lower pyrite content. Additionally, water plays a crucial role as a reaction medium in the oxidation process, with its infiltration rate directly affecting the initial oxidation rate. These findings provide important insights for preventing geological hazards in high-speed rail projects under similar geological conditions.